A new species of ladyfish, of the genus Elops (Elopiformes: Elopidae), from the western Atlantic Ocean - Mcbride, Richard S.; Rocha, Claudia R.; Ruiz-Carus, Ramon; Bowen, Brian W. (Zootaxa, 2010)
v This paper describes Elops smithi, n. sp., and designates a lectotype for E. saurus. These two species can be separated from the five other species of Elops by a combination of vertebrae and gillraker counts. Morphologically, they can be distinguished from each other only by myomere (larvae) or vertebrae (adults) counts. Elops smithi has 73–80 centra (total number of vertebrae), usually with 75–78 centra; E. saurus has 79–87 centra, usually with 81–85 centra. No other morphological character is known to separate E. smithi and E. saurus, but the sequence divergence in mtDNA cytochrome b (d = 0.023–0.029) between E. smithi and E. saurus is similar to or greater than that measured between recognized species of Elops in different ocean basins. Both species occur in the western Atlantic Ocean, principally allopatrically but with areas of sympatry, probably via larval dispersal of E. smithi by oceanographic currents.